PIECES ANALYSIS OF SYSTEM IMPLEMENTATION DRUG PROCUREMENT ACCOUNTING INFORMATION IN RSUD KOTA SURAKARTA - Nugroho Wisnu Murti; Fitriana Elin Puspita (STIE AUB Surakarta, 2019)
This study aims to analyze inventory accounting information systems in the procurement, storage, and distribution of medicines at Surakarta City Hospital, especially Pharmacy Installation in order to improve the effectiveness of the inventory accounting system applied. By analyzing the system using PIECES analysis to find out the problems, weaknesses of the procurement system. Data collection is done by interviews, observation and documentation. Basedon the research that has been done, the researcher can conclude that the inventory accounting system in the procurement, storage, and distribution of medicines applied in the Surakarta City Public Hospital Pharmacy Installation has been well implemented.